Non-invasive Assessment of Systolic and Diastolic Cardiac Function During Rest and Stress Conditions Using an Integrated Image-Modeling Approach - Casas, Belén; Viola, Federica; Cedersund, Gunnar; Bolger, Ann F.; Karlsson, Matts; Carlhäll, Carl-Johan; Ebbers, Tino (Frontiers in Physiology, 2018)
Background: The possibility of non-invasively assessing load-independent parameters characterizing cardiac function is of high clinical value. Typically, these parameters are assessed during resting conditions. However, for diagnostic purposes, the parameter behavior across a physiologically relevant range of heart rate and loads is more relevant than the isolated measurements performed at rest. This study sought to evaluate changes in non-invasive estimations of load-independent parameters of left-ventricular contraction and relaxation patterns at rest and during dobutamine stress. Methods: We applied a previously developed approach that combines non-invasive measurements with a physiologically-based, reduced-order model of the cardiovascular system to provide subject-specific estimates of parameters characterizing left ventricular function. In this model, the contractile state of the heart at each time point along the cardiac cycle is modeled using a time-varying elastance curve. Non-invasive data, including four-dimensional magnetic resonance imaging (4D Flow MRI) measurements, were acquired in nine subjects without a known heart disease at rest and during dobutamine stress. For each of the study subjects, we constructed two personalized models corresponding to the resting and the stress state. Results: Applying the modelling framework, we identified significant increases in the left ventricular contraction rate constant (from 1.5±0.3 to 2±0.5 (p=0.038)) and relaxation constant (from 37.2±6.9 to 46.1±12 (p=0.028)). In addition, we found a significant decrease in the elastance diastolic time constant from 0.4±0.04 s to 0.3±0.03 s (p=0.008). Conclusions: The integrated image-modelling approach allows the assessment of cardiovascular function given as model-based parameters. The agreement between the estimated parameter values and previously reported effects of dobutamine demonstrates the potential of the approach to assess advanced metrics of pathophysiology that are otherwise difficult to obtain non-invasively in clinical practice.